Proses Start Up Produksi Bioetanol dari Tepung Sorghum Menggunakan Reaktor Anaerobik Berpenghalang - Rosadela Lucky Artha; Ade Tia Suryani; Margono Margono; Mujtahid Kaavessina; Endah Retno Dyartanti (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Sorghum bicolor grain is a potential raw material for bioethanol production. Sorghum bicolor grain contain a high starch, i.e. 65 – 70% by weight. This is much higher than cassava starch. The objective of this research is to produce bioethanol from Sorghum bicolor grain using Simultaneous Saccharification and Fermentation Process in Anaerobic Baffled Reactor (ABR) and biocatalyst of co-immobilisation yeast-glucoamylase. ABR is a reactor which has 4 compartment and has working volume of 2,5 L respectively. These experiments focused to study start-up process of the fermentation.. The start up was initiated with batch process for 16 hours followed by continuous fermentation in order to get steady process.  During start-up process showed increasing concentration of bioethanol and decreasing of reducing sugar as well as total sugar. The results show that the best ethanol concentration in start-up process were 1,277 g/L for compartment A, 1,572 g/L for compartment B, 1,69 g/L  for compartment C, and 1,454 g/L for compartment D at 19 hours of fermentation time.